THE IMPORTANCE OF SPORTS CLUBS OF STUDENTS IN HIGHER EDUCATION : Zh.Zh. Atamuradov - Atamuradov, Jamshid (Центр Научных Публикаций (buxdu.uz), 2021)
The article stresses the importance of organizing sports clubs in higher education. Keywords: physically strong, intellectually mature, healthy lifestyle, healthy.